Tanggung Jawab PDAM Kabupaten Gianyar dalam Hal Tidak Mengalirnya Air Secara Sepihak Kepada Konsumen dalam Perspektif Undang-Undang Nomor 8 T Ahun 1999 - Komang Adika Bayu Mahendra; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
Water is the most important thing in household and industry. The problem that often occurs in the community regarding water is the non-flow of water, the negligence of PDAM officers, where the consumer is the most at risk of experiencing losses. This study aims to examine the sanctions imposed on PDAM Gianyar Regency for consumer losses for the act of not draining water unilaterally and analyzing legal protection for consumers due to losses for not flowing water unilaterally. The method used is the research is normative law with legislation and conceptual approach. Sources of data are primary legal materials and secondary legal materials, this data was obtained through interviews and literature study. Furthermore, the data is processed and analyzed using a qualitative descriptive method. The results of the study indicate that consumer protection is regulated in Law number 8 of 1999. The responsibility of the PDAM if they receive complaints from consumers, namely the PDAM technician directly goes to the consumer's area to check the cause and point of the problem so that water in the area or consumer's house does not flow. So that the PDAM can quickly deal with it. Legal remedies taken by business actors or PDAMs if there is a dispute, the PDAM prioritizes non-litigation by means of negotiation and mediation by deliberation so as to obtain a joint decision.